2004
DOI: 10.1111/j.1365-2273.2004.00852.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of vestibular schwannomas - second review of a prospective longitudinal study

Abstract: Vestibular schwannomas have been traditionally managed with microsurgical removal and in recent years, stereotactic radiotherapy. However, there is a group of patients in whom a conservative management approach might represent a desirable alternative. The aim of this study was to determine the natural history and outcome following the conservative management of 72 patients with unilateral vestibular schwannomas. This is a prospective cohort review of a previously published group of patients [Clin. Otolaryngol.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 38 publications
(70 reference statements)
6
66
0
2
Order By: Relevance
“…Studies have shown that the majority of vestibular schwannomas tend to grow slowly (38-43%) (9, 10). Conservative management of these tumors is appropriate in select cases, such as in patients with advanced age, poor general health or small tumors (3,11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that the majority of vestibular schwannomas tend to grow slowly (38-43%) (9, 10). Conservative management of these tumors is appropriate in select cases, such as in patients with advanced age, poor general health or small tumors (3,11).…”
Section: Discussionmentioning
confidence: 99%
“…MRI is the imaging technique used in the conservative management of vestibular schwannomas (2,3). T1W sequences with a gadolinium-based contrast agent are the gold standard for the initial detection and follow-up examinations of these tumors (5, 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mientras que la observación con RNM seriadas se recomienda frecuentemente para los pacientes mayores con tumores pequeños 9,26 , en los pacientes jóvenes con buen estado de salud y tumores grandes se recomienda normalmente la resección quirúrgica.…”
Section: Estado Actual Del Tratamiento Del Svunclassified
“…57,81 The data, however, do not always show a linear correlation between the rate of tumor growth and deterioration of hearing. 38,39,82,96,104 …”
Section: Mechanism Of Hearing Loss In Vsmentioning
confidence: 99%